Syntheses of a Hyperbranched Polymer and Its Performance on Enhanced Oil Recovery - Qiao, Sanyuan; Liu, Qingwang; Zhang, Xian; Che, Hongchang (Frontiers in Chemistry, 2021)
A hyperbranched carboxylate type polymer was synthesized through esterification and carboxymethylation and its performance on enhanced oil recovery was experimentally evaluated. The optimum condition for esterification was 8 hours at 120℃, 3% PTSA as the catalyst and 9:1 mol ratio of the AB2 intermediate and trimethylolpropane. The optimum condition for carboxymethylation was 4 hours at 80℃. The critical micelle concentration of the hyperbranched polymer was 433.63 mg/L, the Krafft point was 5℃, the surface tension was lowered to 28 mN/m. In the range of 400-500 mg/L concentration, the adsorption onto the oil sands surface achieved equilibrium and micellar solubilization reached 600mL/mol. The interfacial tension can be lowered to 10-2mN/m level by single use of the hyperbranched polymer, and the value further decreased to 10-3mN/m level while being formulated with sodium dodecylsulfate or NaOH. The oil recovery of water flooding was further enhanced by the single use of hyperbranched polymer or the combination of hyperbranched polymer/sodium dodecylsulfate. The latter exhibited more prosper advantages in low permeability reservoirs.